TINDAK TUTUR DIREKTIF DALAM FILM 'JOJO RABBIT' KARYA TAIKA WAITITI - Ramadhan, Muhammad Rizqi; Widyahening, Ch. Evy Tri (English Education Department Slamet Riyadi University Surakarta, 2024)
This research was conducted to analyze and find out the speech act that occurred in ‘Jojo Rabbit’ movie. This research also analyzed (1) the locutionary act that found in main character’s utterances in ‘Jojo Rabbit’ movie, (2) the illocutionary act that found in main character’s utterances in ‘Jojo Rabbit’ movie, (3) the perlocutionary act that found in main character’s utterances in ‘Jojo Rabbit’ movie, (4) the directive speech act that found in main character’s utterances in ‘Jojo Rabbit’ movie. The researcher conducted this research in the library of Slamet Riyadi University. Method that used in this research was qualitative descriptive and data in this research were collected through documentation and observation. The researcher watched the ‘Jojo Rabbit’ movie several times, read the transcript of the ‘Jojo Rabbit’ movie, and then marked the dialogue and identified the locutionary act, illocutionary act, perlocutionary act, and directive speech act. The findings of this research showed that in ‘Jojo Rabbit’ movie, there were 205 utterances of locutionary act. There were 205 utterances of illocutonary act, classified into 91 of assertives, 10 of declaratives, 71 of directives, 11 of commisives, 22 of expressives. There were 202 utterances of perlocutionary act, classified into 87 times to inform, 24 times to convince, 11 times to confess, 21 times to cause the listener to do something, 48 times to cause the listener to answer question, 5 times to greet, and 6 times to approve. There were 71 utterances that considered as directive speech act, classified into 15 of commanding, 44 of questioning, 3 of prohibiting, 1 of permissioning, and 8 of requesting. The research analyzed speech acts in the movie